2020
DOI: 10.21203/rs.3.rs-51786/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-Genome-Wide Analysis of Pantoea Ananatis Identified Genes Linked to Pathogenicity in Onion

Abstract: Background: Pantoea ananatis is a member of a Pantoea spp. complex that causes center rot of onion, which significantly affects onion yield and quality. This pathogen does not have typical virulence factors like type II or type III secretion systems but appears to require a biosynthetic gene-cluster, HiVir/PASVIL (located chromosomally), for a phosphonate secondary metabolite, and the onion-virulence regions, OVR (localized on a megaplasmid), for onion pathogenicity and virulence, respectively. Results: We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 42 publications
(58 reference statements)
1
7
2
Order By: Relevance
“…cepacicola PNA 03-3 is more closely related to P. ananatis (LMG 2665 T ), which is reflected in the core SNP-based phylogeny. The WgMLST, an extended concept of MLST is complementary to PAV based phylogenetic analysis [8]. As expected, we observed similar pattern of phylogenetic classification of strains both with PAVs-and wgMLST-based phylogeny.…”
Section: An Open Pan-genome Of Pantoea Stewartii Subsp Indologenessupporting
confidence: 84%
See 3 more Smart Citations
“…cepacicola PNA 03-3 is more closely related to P. ananatis (LMG 2665 T ), which is reflected in the core SNP-based phylogeny. The WgMLST, an extended concept of MLST is complementary to PAV based phylogenetic analysis [8]. As expected, we observed similar pattern of phylogenetic classification of strains both with PAVs-and wgMLST-based phylogeny.…”
Section: An Open Pan-genome Of Pantoea Stewartii Subsp Indologenessupporting
confidence: 84%
“…In the current study we identified 3,546 core genes, 5 to 382 cloud genes and 394 to 703 shell genes. A similar study using 81 P. ananatis strains identified 3,153 core genes and cloud genes ranging from 1000 to 6,808 [8]. We observed a stark difference in the number of cloud genes when compared to our earlier study on P. ananatis.…”
Section: Pantoea Stewartii Subsp Indologenes Pan-genome and Horizontal Gene Transfercontrasting
confidence: 53%
See 2 more Smart Citations
“…As a result, several studies have been conducted to comprehensively explore features specific to each genome. The most widely explored genomic variants used in genome-wide studies are single nucleotide polymorphisms (SNPs) that are utilized in both prokaryotes [ 8 ] and eukaryotes [ 9 , 10 , 11 , 12 , 13 , 14 ]. Another widely used technique to explore variations in prokaryotic genomes is the use of presence and absence variants (PAVs).…”
Section: Introductionmentioning
confidence: 99%